(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The development ofany nation depends on its educational system and it is proved that education isthe key to human progress and social change. Education is a powerful tool forempowerment of individual. It helps in developing confidence in individual and community about their own capacities, inherent strengths to shape their lives and thus enhance the inner strength- intellectual, political, social and economicagainst oppression, exclusion and discrimination.